2010
DOI: 10.2183/pjab.86.588
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of Hepatocyte Growth Factor (HGF) and its significance for cell biology, life sciences and clinical medicine

Abstract: It has been more than 25 years since HGF was discovered as a mitogen of hepatocytes. HGF is produced by stromal cells, and stimulates epithelial cell proliferation, motility, morphogenesis and angiogenesis in various organs via tyrosine phosphorylation of its receptor, c-Met. In fetal stages, HGF-neutralization, or c-Met gene destruction, leads to hypoplasia of many organs, indicating that HGF signals are essential for organ development. Endogenous HGF is required for self-repair of injured livers, kidneys, lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
371
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 440 publications
(413 citation statements)
references
References 136 publications
8
371
0
11
Order By: Relevance
“…However, another downstream effector of PPARγ, HGF, is also likely to act as a 'guardian' in MS, in addition to adiponectin. Previous studies suggested that HGF mediates multiple various biological effects in various cells including anti-fibrotic, anti-inflammatory and anti-apoptotic activities (14). The present study clearly demonstrated that the anti-metabolic effects of irbesartan were largely mediated by the PPARγ-HGF pathway, with the exception of Ang II blockade.…”
Section: Discussionsupporting
confidence: 73%
“…However, another downstream effector of PPARγ, HGF, is also likely to act as a 'guardian' in MS, in addition to adiponectin. Previous studies suggested that HGF mediates multiple various biological effects in various cells including anti-fibrotic, anti-inflammatory and anti-apoptotic activities (14). The present study clearly demonstrated that the anti-metabolic effects of irbesartan were largely mediated by the PPARγ-HGF pathway, with the exception of Ang II blockade.…”
Section: Discussionsupporting
confidence: 73%
“…1,2 Systemic administration of HGF has various beneficial effects in renal failure models in experimental animals. In a mouse model of obstructive nephropathy, for example, HGF attenuates the progression of interstitial fibrosis with a concomitant reduction in tubular apoptosis and an increase in tubular proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This receptor is also proposed to be involved in systemic clearance of HGF. For example, after down-regulation, i.e., reduction of the receptor density on the cell surface, induced by the injection of a relatively high dose of HGF, the total body clearance of 125 I-HGF first decreased, but subsequently increased due to recruitment of c-Met/HGF receptor to the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of these miRNAs is required for the mesenchymal to epithelial transition, a key component of the initiation phase of reprogramming [46]. On this regard, it has been reported that BMP4 regulates the expression level of miR210 and this effect contributes to osteoblastic differentiation [47]. miR199a(*) is an early responsive target of BMP2 during chondrogenesis [48] and several miRNAs are regulated in the BMP2 induced osteogenesis [49].…”
Section: Activation Of Canonical and Non-canonical Pathwaysmentioning
confidence: 99%